Thermodynamic models for water sorption by grape skin and pulp - Gabas, A. L.; Telis-Romero, J.; Menegalli, F. C. (Marcel Dekker Inc, 1999)
The enthalpy-entropy compensation theory was applied to water sorption for grapes of Italy variety. The moisture sorption isotherms were analyzed using the static gravimetric method at 35, 40, 50, 60, 70 and 75 degrees C. For isotherms construction, the skin and pulp of the grape were used separately and it was possible to observe significant differences. The GAB equation was fitted to the experimental data, using direct nonlinear regression analysis; the agreement between experimental and calculated values was satisfactory. The net isosteric heat or enthalpy of water sorption, determined from the equilibrium sorption data, showed a different behavior when compared with other works, as it was obtained for skin and pulp separately. Plots of Delta h vs Delta S for skin and pulp provided the isokinetic temperatures T-Bs = 423.2 +/- 27.6 K and T-Bp = 424.5 +/- 25.3 K, respectively, indicating an enthalpy-controlled desorption process over the whole range of moisture content considered.
Keywords: enthalpy; entropy; grape; heat sorption; isotherms; moisture content